Ultra Petita Practices in Regional Head Election Disputes before the Constitutional Court of Indonesia - Adithiya Diar; Saputra, Beny; Hartati (Jurnal Media Hukum, 2026)
This study examines the tension between legal certainty and substantive justice in regional election disputes in Indonesia, focusing on the Constitutional Court’s application of the ultra petita doctrine. It analyzes how the Court balances procedural law with moral considerations to ensure fair and legitimate electoral outcomes. Using normative legal research, the study applies three approaches: a conceptual approach to explore principles such as ultra petita, procedural justice, and substantive justice; a statutory approach to review relevant laws, including Law No. 10 of 2016 and Constitutional Court Regulation No. 3 of 2024; and a case approach examining key decisions, including No. 41/PHPU.D-VI/2008 and No. 313/PHPU.BUP-XXIII/2025. The findings show that the Court often prioritizes substantive justice over strict legal certainty, particularly in cases involving vote-buying or electoral manipulation. Through ultra petita rulings, the Court addresses legal gaps, safeguards constitutional rights, and upholds democratic integrity. The study concludes that the Constitutional Court has evolved from a guardian of statutory texts into a moral interpreter of the Constitution. To preserve legitimacy and predictability, clearer and proportionate guidelines for exercising ultra petita powers in regional election disputes are recommended.